Pengaruh Penambahan Pasir dan Kompos terhadap Pertumbuhan Bibit Kaliandra dan Beberapa Sifat Tanah - I WAYAN NARKA; I WAYAN DANA ATMAJA (Fakultas Pertanian Universitas Udayana, 2023)
Study on Effect Applications Sand and Compost on growth of kaliandra and soil properties. The purpose of this study was to determine the effect of giving sand and compost on growth of kaliandra and soil properties. The design used was a factorial randomized block design with 3 replications. The giving of sand factor consisted of 3 levels: P0 = no sand, P1 = 10% sand and P2 = 30% sand. The compost factor consisted of 3 levels: K0 = without compost, K1 = 10 tons of compost ha-1, and K2 = 20 tons of compost ha-1. The observation of growth of kaliandra consisted : plant height, fresh weight of shoot and root of kaliandra, dry weight of shoot and root of kaliandra. Parameters of soil properties were observed: bulk density, C-organic matter content, Nitrogen content of soil and available of Phosphor dan Kalium of soil. The results of research showed that, no interaction between the treatment of giving sand and compost on the soil properties and growth of kaliandra, while the single treatment of compost had a significant effect on growth of kaliandra. The treatment of giving sand has not shown a significant effect, both on soil properties and on growth of kaliandra.